Investigating the Promise of a Tier 2 Sixth-Grade Fractions Intervention. (November 2022) - Clarke, Ben; Nelson, Nancy J.; Ketterlin Geller, Leanne; Kosty, Derek; Smolkowski, Keith; Lesner, Taylor; Furjanic, David; Fien, Hank
This pilot study examined the promise of a Tier 2 Grade 6 intervention program for students at risk for difficulties in mathematics. The study utilized a quasi-experimental design. The final sample included 112 students in treatment (Promoting Algebra Readiness) and 86 students in control (standard district practice) conditions. The Promoting Algebra Readiness program consisted of 93 lessons across four strands focused on key concepts and applications of fractions. Measures of mathematics achievement were collected at pretest and posttest. Feasibility and usability data indicated favorable impressions by users and strong levels of implementation fidelity. Gain scores of treatment students were significantly greater than those of control peers on two of four proximal measures of mathematics achievement. Positive nonsignificant effects were found on additional proximal and distal measures. Implications for educators delivering instruction for at-risk students in multitier service delivery models are discussed.